Analisis partisipasi masyarakat dalam membayar pajak bumi dan bangunan di Kelurahan Warujayeng Kecamatan Tanjunganom Kabupaten Nganjuk - Miladiah, Laili; Meirini, Dianita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
It doesn’t matter whether it is a developed country, a developing country, or a developing country, the rapid development of the country never stops. Indonesia is one of the developing countries that keeps improving the development of the country. Development requires money, one of which comes as a result of people's aspirations: property taxes and building taxes. This study aims to analyze community participation in payment of land and building tax (PBB) in Warjayen Village, Tanjungganom District, Nganjuk District. The research method used is a qualitative method of descriptive research type. The results of this study show that community participation in Warjaen Village is sub-optimal. A factor that hinders the payment of property and building taxes is the lack of public awareness of their tax obligations due to lack of education and village government involvement. In other words, community engagement is not good because the level of communication, attitudes and responsibilities of tax officials are not optimal.